Investigation of strained InGaAs layers on GaAs substrate - Jasik, Agata; Sass, Jerzy; Mazur, Krystyna; Wesołowski, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
A set of In0.13Ga0.87As layers of various thicknesses on GaAs substrate has been grown by low pressure metalorganic vapour phase epitaxy (LP MOVPE). The initial stage of relaxation process has been investigated and critical layer thickness (CLT) has been determined. The investigations were performed by applying atomic force microscopy (AFM), high resolution X-ray diffractometry (HR XRD) with conventional and synchrotron radiation. The value of CLT determined by AFM observations agrees with that obtained from diffuse scattering measurements. The value is in agreement with HR XRD results.
Optica Applicata, Vol. 37, 2007, nr 3, s. 237-242
Keywords: optyka; low pressure metalorganic vapour phase epitaxy (LP MOVPE); strained InGaAs layer; critical layer thickness; high resolution X-ray diffractometry (HR XRD); diffuse scattering; atomic force microscopy (AFM); misfit dislocation; plastic relaxation